2021
DOI: 10.3390/molecules26030519
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Compound of Efavirenz and γ-Cyclodextrin: Solid State Studies and Effect on Solubility

Abstract: Efavirenz is an antiretroviral drug of widespread use in the management of infections with human immunodeficiency virus type 1 (HIV-1). Efavirenz is also used in paediatrics, but due to its very poor aqueous solubility the liquid formulations available resort to oil-based excipients. In this report we describe the interaction of γ-cyclodextrin with efavirenz in solution and in the solid state. In aqueous solution, the preferential host–guest stoichiometry was determined by the continuous variation method using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…In fact, due to the effect of γ-CD, the phased mass loss of the γ-CD-ITC inclusion complexes showed an evident slope between 132 °C and 300 °C, which delayed their volatilization. A similar study of the inclusion complex of efavirenz with γ-CD was reported by Braga et al [ 36 ]. In addition, both BITC and carvacrol inclusion complexes encapsulated in β-CD have high thermal stabilities [ 34 , 37 ].…”
Section: Resultssupporting
confidence: 68%
“…In fact, due to the effect of γ-CD, the phased mass loss of the γ-CD-ITC inclusion complexes showed an evident slope between 132 °C and 300 °C, which delayed their volatilization. A similar study of the inclusion complex of efavirenz with γ-CD was reported by Braga et al [ 36 ]. In addition, both BITC and carvacrol inclusion complexes encapsulated in β-CD have high thermal stabilities [ 34 , 37 ].…”
Section: Resultssupporting
confidence: 68%
“…FT-IR is widely used to analyze the interactions between guest molecules and CD in the solid-state (Braga et al. 2021 ). FT-IR spectra of the raw KME, HP-β-CD, physical mixtures, and KME/HP-β-CD were shown in Figure 4(C) .…”
Section: Resultsmentioning
confidence: 99%
“… 1 H → 13 C CP-MAS NMR spectra of ( a ) Efavirenz (EFV), ( b ) γ-CD, ( c ) (γ-CD) 3 @(EFV) 2 , and ( d ) γ-CD@EFV. Adapted from [ 55 ], licensed under CC BY 4.0. ( e ) Image on the right presents 1 H → 13 C CP NMR pulse sequence.…”
Section: Ssnmr Approaches For the Analysis Of Cyclodextrin Complexesmentioning
confidence: 99%